2015
DOI: 10.1093/hmg/ddv284
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of the abnormal skeletal phenotype in Ts65Dn Down syndrome mice using genetic and therapeutic modulation of trisomicDyrk1a

Abstract: Trisomy 21 causes skeletal alterations in individuals with Down syndrome (DS), but the causative trisomic gene and a therapeutic approach to rescue these abnormalities are unknown. Individuals with DS display skeletal alterations including reduced bone mineral density, modified bone structure and distinctive facial features. Due to peripheral skeletal anomalies and extended longevity, individuals with DS are increasingly more susceptible to bone fractures. Understanding the genetic and developmental origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 54 publications
5
72
3
Order By: Relevance
“…Three important candidate factors that may account for differences are dosage, the developmental timing of the treatment, or interactions with other substances included in some EGCG supplements. We have shown that a three week treatment of ~10 mg/kg/day EGCG improved skeletal deficits in Ts65Dn mice (Blazek et al, 2015). A higher concentration of EGCG may be necessary to significantly improve cognitive deficits in the Ts65Dn mouse.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Three important candidate factors that may account for differences are dosage, the developmental timing of the treatment, or interactions with other substances included in some EGCG supplements. We have shown that a three week treatment of ~10 mg/kg/day EGCG improved skeletal deficits in Ts65Dn mice (Blazek et al, 2015). A higher concentration of EGCG may be necessary to significantly improve cognitive deficits in the Ts65Dn mouse.…”
Section: Discussionmentioning
confidence: 77%
“…Previous work in our lab using a three-week low-dose EGCG treatment (~10 mg/kg/day) during adolescence resulted in improvements in skeletal deficits in trisomic mice (Blazek, Abeysekera, Li, & Roper, 2015). A similar dose (~9 mg/kg/day in capsule form) was used in the human study that showed improvements in cognition and more positive caregiver reports (De la Torre et al, 2014).…”
Section: Individuals With Ds Display Developmental Alterations In Bramentioning
confidence: 96%
“…For skeletal parameters in DS mouse models, we and others have identified significant deficits in BMD, trabecular bone parameters (thickness, separation and number) and cortical bone measures in Ts65Dn mice compared to euploid control mice [17]. Significant deficits in mineral apposition rate (MAR), bone formation rate (BFR), and strength properties in trisomic mice compared to controls were also observed [17, 26, 27]. …”
Section: Introductionmentioning
confidence: 96%
“…EGCG is a small molecular inhibitor of DYRK1A activity and is thought to function by binding to the ATP binding domain of the protein thereby inhibiting its kinase activity [42, 43]. EGCG, either alone or in supplements containing EGCG, has been tested as a potential therapy in mouse models of DS [23, 26, 4448] and in humans with DS [45, 49, 50]. In one recent study [45] trisomic mice were given an EGCG-containing supplement (Life Extension ® Mega Green Tea Extract, Lightly Caffeinated) in drinking water that was reported to deliver 2–3 mg of EGCG per day per mouse (i.e., a daily dosage of ~80–120 mg/kg [for a 25 g mouse] that would yield a final effective dosage of ~40–60 mg/kg per day after accounting for the known degradation of EGCG [23, 44]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation